Drivers of Large Recessions and Monetary Policy Responses - Giovanni Melina; Stefania Villa (Center for Economic Studies and ifo Institute (CESifo), 2023)
Shocks to capital utilization are introduced in a structural macroeconomic closed-economy model with financial frictions to capture disruptions on the ability of the capital stock to provide capital services used in production. Estimates for the Euro Area and the United States show that these shocks were among the most important drivers of the output contraction during the Global Financial Crisis and the COVID-19 Crisis, while financial shocks were more relevant during the Global Financial Crisis. Thanks to the timely and strong intervention of the European Central Bank and the U.S. Federal Reserve, monetary policy shocks exerted a sizable positive contribution to output and inflation during the COVID-19 Crisis.
Keywords: E40; E50; E60; 330; Covid-19; Global Financial Crisis; Great Lockdown; monetary policy; capital utilization